PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN PAVING BLOCK DARI LIMBAH PLASTIK DI WISATA TAMAN BUNGA IMPIAN OKURA KELURAHAN TEBING TINGGI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Nurhalizah Nurhalizah; Jaspar Jas; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines community empowerment through the manufacture of paving blocks from plastic waste in the flower garden impian okura Pekanbaru. This research use descipitive qualitative approach. Research subjects will be determined based on purposive sampling, there are 5 (five) informants in this study. Data collection is done by data reducation; data display; and also conclusion drawing/verifying. The results of the study show that 1) The preparatory stage in conduction the empowerment activities is good, 2) The Plainning stage in conduction the empowerment activities is good, 3) The implementation phase stage in conduction the empowerment activities is good, 4) Evalution stage in conduction the empowerment activities is good.Key Words: Community Empowerment, Paving Block, Plastic Waste